The Association between Healthy Diet and Burnout Symptoms among Finnish Municipal Employees - Penttinen Markus A; Virtanen Jenni; Laaksonen Marika; Erkkola Maijaliisa; Vepsalainen Henna; Kautiainen Hannu; Korhonen Päivi (MDPI, 2022)
Background: Burnout is an undesirable mental condition, which may have a negative impact on individuals' health and work ability. This study aimed to evaluate the relationship between diet and burnout symptoms among female public sector employees. Methods: A cross-sectional study was conducted in 2015 among 630 female employees from 10 municipal work units of the city of Pori, Finland. Burnout symptoms were assessed with the Bergen Burnout Indicator (BBI). The consumption of food items was determined using the food frequency questionnaire (FFQ). The main food groups were categorized into healthy and unhealthy foods based on the Nordic Nutrition Recommendations for a healthy and balanced diet. Results: In multivariate linear regression analysis, consumption of healthy food items had an inverse relationship with the severity of burnout symptoms independently of age, education years, physical activity, and depressive symptoms. De-tailed analysis revealed that subjects with lower BBI score consumed more often low-fat dairy produce, vegetables, fruit and berries, vegetable food, and white meat. Conclusions: Frequent consumption of healthy food items is associated with low level of burnout symptoms. Our results emphasize the importance of diverse and balanced healthy diet to promote work well-being.